2006
DOI: 10.4049/jimmunol.177.11.7833
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for NK Cell Subsets Based on Chemokine Receptor Expression

Abstract: To help understand the role of chemokines in NK cell trafficking, we determined the chemokine receptor profiles of three different human NK cell lines and freshly isolated primary human NK cells. The cell lines overlapped in their chemokine receptor profiles: CXCR3 and CXCR4 were expressed by all three lines, whereas CCR1, CCR4, CCR6, CCR7, and CX3CR1 were expressed by only one or two of the lines, and no other chemokine receptors were detected. Freshly isolated primary NK cells were found to express CXCR1, CX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
131
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(145 citation statements)
references
References 20 publications
(14 reference statements)
12
131
0
1
Order By: Relevance
“…DC maturation induced by IFN-g/FMKp led to an enhanced (41.5-fold increase in chemiluminescence) secretion of eleven chemokines as compared with TNF-a/PGE2-induced maturation. These chemokines included CCL5, CXCL10 and CCL19 to which NK cells can respond [23][24][25]. Quantification with ELISA confirmed that these chemokines were indeed produced by IFN-g/FMKp-matured DC and not by TNF-a/PGE2-matured DC (Fig.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…DC maturation induced by IFN-g/FMKp led to an enhanced (41.5-fold increase in chemiluminescence) secretion of eleven chemokines as compared with TNF-a/PGE2-induced maturation. These chemokines included CCL5, CXCL10 and CCL19 to which NK cells can respond [23][24][25]. Quantification with ELISA confirmed that these chemokines were indeed produced by IFN-g/FMKp-matured DC and not by TNF-a/PGE2-matured DC (Fig.…”
mentioning
confidence: 73%
“…In steady-state conditions, the CD56 bright CD16 À NK-cell subpopulation has been reported to express CCR7 [25], which allows them to migrate into lymph nodes [26]. However, in response to IL-18-producing monocytes, induction of CCR7 has also been observed on CD56 dim CD16 1 NK cells [6].…”
Section: Dc-dependent Induction Of Ccr7 Expression On Nk Cellsmentioning
confidence: 99%
“…Intestinal epithelial cell lines, IEC6 (rat, passage 36-46) and CaCo-2 (human, passage [30][31][32][33][34][35][36][37][38][39][40], were grown on Lab-Tek I chamber slides and stained for CXCR3 as described above. To localize CXCR3 expression in intestinal tissues, 4-µm sections were prepared, and laser capture microdissection (mouse tissue) or immunohistochemistry (human tissue) were performed as previously described.…”
Section: Cxcr3 Expression In Intestinal Cell Lines and Tissuesmentioning
confidence: 99%
“…CD56 bright NK cells preferentially accumulate in the T cell area of the lymph node, presumably through their selective expression of CCR7 and CD62L (4,5). The developmental relationship between CD56 dim and CD56 bright NK cells is not clear, and these two subpopulations of NK cells may represent two developmentally distinct subsets.…”
mentioning
confidence: 99%